Cholecystectomy under thoracic epidural anaesthesia for patient with severe intra‐pulmonary shunt. Issue 3 (8th March 2020) - Frankel, Agustina; Ferris, Rebekah; Hodgkinson, Peter; Ellender, Claire M.
Abstract: Pulmonary arteriovenous malformations are common in patients with hereditary haemorrhagic telangiectasia and can be associated with significant hypoxia and intra‐pulmonary shunt. We present a case of a young man with a known 57% calculated shunt requiring abdominal surgery and the multidisciplinary decisions required in the preoperative period to minimize post‐operative complications. Abstract : Pulmonary arteriovenous malformations are common in patients with hereditary haemorrhagic telangiectasia and can be associated with significant hypoxia and intra‐pulmonary shunt. We present a case of a young man with a known 57% calculated shunt requiring abdominal surgery and the multidisciplinary decisions required in the preoperative period to minimize post‐operative complications.